9(2x+x)-4x=3x-10

Simple and best practice solution for 9(2x+x)-4x=3x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2x+x)-4x=3x-10 equation:


Simplifying
9(2x + x) + -4x = 3x + -10

Combine like terms: 2x + x = 3x
9(3x) + -4x = 3x + -10

Remove parenthesis around (3x)
9 * 3x + -4x = 3x + -10

Multiply 9 * 3
27x + -4x = 3x + -10

Combine like terms: 27x + -4x = 23x
23x = 3x + -10

Reorder the terms:
23x = -10 + 3x

Solving
23x = -10 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
23x + -3x = -10 + 3x + -3x

Combine like terms: 23x + -3x = 20x
20x = -10 + 3x + -3x

Combine like terms: 3x + -3x = 0
20x = -10 + 0
20x = -10

Divide each side by '20'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| -w/7=32 | | s(t)=81-16t^2 | | 8-8=9x+3x | | 12x^5-8x^4+6x^3= | | 2-3a+5=-4a+4 | | 4/3*3.14 | | -2+7x-3x^2=0 | | 5x-179=-11x+61 | | b+b+b+b-2+b-4+b-6+b-8+b-10+b-12=156 | | 2m^2+100=20 | | 2.00x-15.00-11= | | 28x^2-108x-160=0 | | 24=h/-12 | | -5y=17 | | -51-x=27-4x | | 3n-18=2n+12 | | 3b+(6b-2)=156 | | 7/8x==49 | | 45/18=10/t | | 8=25m | | 156=3b+6b-2 | | 5n-24=60 | | 0=170-3x | | (73-x)+x=73 | | -6x^2-24x-25=y | | 52=m/5 | | 6x+5=5(3x-8) | | 5-2(x+3)=9 | | 3+2v=-9 | | 81-4x=x | | 3a-2b=3b-7-2a | | 6x-1=11x-12 |

Equations solver categories